Formulation and evaluation of cetuximab functionalized phospholipid modified nanocrystals of paclitaxel for non-small cell lung cancer therapy - Manish Kumar; Pooja Goswami; Abhishek Jha; Manjit Manjit; Amol Parasram Satpute; Biplob Koch; Brahmeshwar Mishra (Scientific Reports)
Abstract Present work aims to prepare Soluplus stabilized, phospholipid-modified, and cetuximab-conjugated paclitaxel nanocrystals (NCs) as stable nanocarriers for targeted drug delivery. The NCs, prepared using concurrent antisolvent precipitation cum cold crystallization method followed by probe sonication, were found to be monodispersed particles with sub-200 nm size. The microscopic analysis uncovered rod and spherical anisotropy for Soluplus stabilized (PTX-NCs) and phospholipid modified (Lipid/PTX-NCs) nanocrystals, respectively. The formation of amorphous PTX-NCs and subsequent coating with phospholipid was confirmed by solid-state characterization using differential scanning calorimetry (DSC), X-ray diffraction (XRD), and Fourier transform Infrared Spectroscopy (FTIR). X-ray Photoelectron Spectroscopic (XPS) analysis, indicated successful conjugation of cetuximab on NCs surface. Lipid coating rendered a sustained drug release behaviour to NCs at physiological pH. In vitro cell line studies confirmed the improved cellular internalization and better apoptosis induction capability of NCs, consequently resulting in enhanced efficacy of PTX against A549 cancer cells. Moreover, in Benzo[a] pyrene-induced lung cancer model, Cmab/Lipid/PTX-NCs showed significant improvement in tumor inhibition potential in comparison to pure PTX. The prepared Cmab/Lipid/PTX-NCs also exhibited improved pharmacokinetics performance, avoided off-target distribution, and showed a reduction in systemic toxicity. The findings of this study indicate the promising potential of the prepared cetuximab-functionalized phospholipid-coated paclitaxel nanocrystals in lung cancer therapy.